Hotspots of Dense Water Cascading in the Arctic Ocean: Implications for the Pacific Water Pathways. Issue 10 (13th October 2020) - Luneva, Maria V.; Ivanov, Vladimir V.; Tuzov, Fedor; Aksenov, Yevgeny; Harle, James D.; Kelly, Stephen; Holt, Jason T.
Abstract: We explore dense water cascading (DWC), a type of bottom‐trapped gravity current, on multidecadal time scales using a pan‐Arctic regional ocean‐ice model. DWC is particularly important in the Arctic Ocean as the main mechanism of ventilation of interior waters when open ocean convection is blocked by strong density stratification. We identify the locations where the most intense DWC events occur and evaluate the associated cross‐shelf mass, heat, and salt fluxes. We find that the modeled locations of cascading agree well with the sparse historical observations and that cascading is the dominant process responsible for cross‐shelf exchange in the boundary layers. Simulated DWC fluxes of 1.3 Sv (1 Sv = 10 6 m 3 /s) in the Central Arctic are comparable to Bering Strait inflow, with associated surface and benthic Ekman fluxes of 0.85 and 0.58 Sv. With ice decline, both surface Ekman flux and DWC fluxes are increasing at a rate of 0.023 and 0.0175 Sv/year, respectively. A detailed analysis of specific cascading sites around the Beaufort Gyre and adjacent regions shows that autumn upwelling of warm and saltier Atlantic waters on the shelf and subsequent cooling and mixing of uplifted waters trigger the cascading on the West Chukchi Sea shelf break. Lagrangian particle tracking of low salinity Pacific waters originating at the surface in the Bering Strait shows that these waters are modified by brine rejection and cooling, and through subsequent mixing become dense enough to reach depths of 160–200 m. Plain Language Summary: In this study we explore dense water cascading, а specific type of bottom‐trapped gravity current. This current of very dense waters originates on the shelves, due to winter cooling and sea ice freezing, and slowly propagates downslope to deep waters. It is specifically important in the Arctic Ocean as the main mechanism of deep water mass formation and carbon storage. We use numerical model of the Arctic Ocean to predict preferable locations of the cascading, its intensity mass, and heat fluxes. Our results are in agreement with available very sparse observations. Our model predicts that with sea ice melting, cascading formation will accelerate. Key Points: Dense water cascading is explored on multidecadal time scales in a 3‐D pan‐Arctic model, presenting good agreement with observations The cross‐shelf water exchanges caused by cascading are estimated as 1.3 Sv of volume flux, thus exceeding the Bering Strait inflow Upwelling of Atlantic waters onto the shelf, followed by subsequent cooling and mixing, trigger cascading on the West Chukchi Sea shelf